Did science cause the industrial revolution? - Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2014)
This paper reviews debates about the role of science and technology before and during the British Industrial Revolution.
Keywords: N13; O10; O30; 330; economic history; science; human capital